2005
DOI: 10.1111/j.1399-0004.2005.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin A is a maternal serum marker for Down's syndrome early in the first trimester

Abstract: Inhibin A is a maternal serum marker for fetal Down's syndrome (DS) in the second trimester. We examined whether inhibin A could be used early in the first trimester. Maternal serum concentrations of inhibin A were determined in 81 controls and 27 cases of fetal trisomy 21 in gestational week 5-11. The log MoM (Multiple of the Median of normal pregnancies) inhibin A concentration in DS pregnancies increased with gestational age (p = 0.001) from a mean log MoM (standard deviation) of -0.1754 (0.3712) (n = 11) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Should BC screening be performed earlier, for example at 8 weeks, then existing detection and false‐positive rates could potentially be improved owing to the larger differences in PAPP‐A levels between affected and unaffected pregnancies23. Additional or alternative markers such as ADAM‐12 and Inhibin A could also be considered24, 25. Whether detection rates can be improved or false‐positive rates reduced will also depend on whether laboratory and ultrasound standards are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Should BC screening be performed earlier, for example at 8 weeks, then existing detection and false‐positive rates could potentially be improved owing to the larger differences in PAPP‐A levels between affected and unaffected pregnancies23. Additional or alternative markers such as ADAM‐12 and Inhibin A could also be considered24, 25. Whether detection rates can be improved or false‐positive rates reduced will also depend on whether laboratory and ultrasound standards are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Under this policy, efficiency rates for DR 5 and FPR 85 of 90.6 and 2.1%, respectively, would be obtained; the screening would be concluded for 77% of the women at the moment when the CT finished; DIA would only need to be measured in 23% of the women at week 13, while there would still remain time to perform CVS if necessary. Previous studies have analyzed the possibility of adding DIA measurement to CT, but have always done so with the aim of making DIA measurement simultaneous with that of PAPP-A and fbHCG, and so have been unable to improve overall screening effectiveness Table 2-Efficiency of the combined test with the added measurement of DIA at 13 weeks, in various sequential formats (nondisclosure, stepwise and contingent), using the population parameters and the proportion of women who began the screening process during each week of gestation in the SURUSS (Wald et al, 2003) Gestational age at which each marker was measured (in weeks) Format of the DIA (Noble et al, 1997), or have only improved it to a slight degree (Christiansen and Nørgaard-Pedersen, 2005;Canick et al, 2006;Palomaki et al, 2007). To the best of our knowledge, the present study is the first one to propose the incorporating DIA measurement (always in week 13) to CT, thus constituting a sequential screening policy during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…At present, DIA is considered an effective secondtrimester marker for chromosome disorders, and it forms part of the quadruple test [together with AFP, uE3 and fbHCG or total human chorionic gonadotrophin (HCG)], and also of the IT. During the first trimester, DIA is detectable in maternal serum from week 5 of gestation, and its concentration increases progressively to peak during week 9 or 10, after which it falls slightly until week 11 or 12 (Christiansen and Nørgaard-Pedersen, 2005). The results of various studies show consistently that DIA concentrations are high among women whose foetuses are affected by DS, although in unequal proportions, by 1.26 MoMs between weeks 11 and 13 , 2.6 MoMs between weeks 13 and 14 (Aitken et al, 1996), 1.52 MoMs between weeks 9 and 11 (Christiansen and Nørgaard-Pedersen, 2005), and 1.036, 1.299 and 1.667 MoMs, in weeks 11,12 and 13 (Spencer et al, 2001), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported that inhibin A is significantly elevated by the late first trimester in trisomy 21 pregnancies. [1][2][3] The addition of inhibin A to the combined test has the potential to increase the detection rate of Trisomy 21 by 3% 4 or reduce the false positive rate by 1.9% 5 over the 10-13 gestational week period. In addition, inhibin A is a potential marker for pre-eclampsia in both the first and second trimesters.…”
mentioning
confidence: 99%